1998
DOI: 10.1521/soco.1998.16.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Direction of Comparison Asymmetries in Relational Judgment: The Role of Linguistic Norms

Abstract: This research documented a linguistic norm account of direction of comparison asymmetry effects in relational judgments (e.g., seeing hyenas as more similar to dogs than dogs are similar to hyenas). The asymmetry effect is magnified by discrepancies in prominence between subject and referent, and has previously been explained using Tversky's (1 977) feature-matching model. Given a linguistic norm to place more prominent objects in the referent position, violation of this norm might reduce sentence clarity, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, while the effect of self‐references remained significant, t (120)=3.97, p <.001, β=0.35, that of comparison focus was eliminated, t (120)=−1.61, p =.11, β=−0.14. In addition, a Sobel test showed that this mediation effect was significantly different from zero, Sobel (Goodman I) z =2.39, p =.017 (Preacher & Leonardelli, 2001).…”
Section: Resultsmentioning
confidence: 95%
“…However, while the effect of self‐references remained significant, t (120)=3.97, p <.001, β=0.35, that of comparison focus was eliminated, t (120)=−1.61, p =.11, β=−0.14. In addition, a Sobel test showed that this mediation effect was significantly different from zero, Sobel (Goodman I) z =2.39, p =.017 (Preacher & Leonardelli, 2001).…”
Section: Resultsmentioning
confidence: 95%
“…The linguistic framing of gender differences may also have a more direct effect on how legitimate existing status differences between women and men appear to be than via the reinforcement of status‐related stereotypes. People tend to communicate as if others shared their category norms (Pratto, Korchmaros, et al, ) and expect comparisons to be framed the same way as they would spontaneously frame them (Roese, Sherman, & Hur, ). When people cannot, or do not, obey these conventions, communication is impaired (Pratto, Korchmaros, et al, ) and cognitive attention is aroused (Holbrook, Krosnick, Carson, & Mitchell, ; Roese et al, ).…”
Section: Effects Of the Comparative Framing Of Gender Differencesmentioning
confidence: 99%
“…People tend to communicate as if others shared their category norms (Pratto, Korchmaros, et al, ) and expect comparisons to be framed the same way as they would spontaneously frame them (Roese, Sherman, & Hur, ). When people cannot, or do not, obey these conventions, communication is impaired (Pratto, Korchmaros, et al, ) and cognitive attention is aroused (Holbrook, Krosnick, Carson, & Mitchell, ; Roese et al, ). Accordingly, comparisons that adhere to linguistic conventions for the respective context should communicate the impression that everything is normal and how it is supposed to be, whereas comparisons that violate these conventions should disrupt the usual flow of communication, including the subtle reinforcement of beliefs about gendered status and power resonating with a conventional framing.…”
Section: Effects Of the Comparative Framing Of Gender Differencesmentioning
confidence: 99%
“…Cognitive reference points were shown to be crucial in similarity judgments (Rosch Brought Tversky & Gati 1978;Roese, Sherman & Hur 1998), judgments of symbolic magnitude (Jamieson & Petrusic 1975;Holyoak 1978), spatial cognition (Sadalla, Burroughs & Staplin 1980;Couclelis, Golledge, Gale & Tobler 1987), social judgments (Holyoak & Gordon 1983;Karylowski, Kornazewski & Motes 2000), negotiations (Kahneman 1992;Kristensen & Gärling 2000), and marketing behaviour (Nunes & Boatwright 2003;Thomas & Menon forthcoming). Cognitive reference points were shown to be crucial in similarity judgments (Rosch Brought Tversky & Gati 1978;Roese, Sherman & Hur 1998), judgments of symbolic magnitude (Jamieson & Petrusic 1975;Holyoak 1978), spatial cognition (Sadalla, Burroughs & Staplin 1980;Couclelis, Golledge, Gale & Tobler 1987), social judgments (Holyoak & Gordon 1983;Karylowski, Kornazewski & Motes 2000), negotiations (Kahneman 1992;Kristensen & Gärling 2000), and marketing behaviour (Nunes & Boatwright 2003;Thomas & Menon forthcoming).…”
Section: Cognitive Reference Pointsmentioning
confidence: 99%